The use of personal contact information for patient communication in ophthalmology - Kelsey M. Donovan; Prem N. Patel; Sandra Hoyek; Celine Chaaya; Hasenin Al-khersan; Kenneth C. Fan; Nicolas A. Yannuzzi; Jayanth Sridhar; Nimesh A. Patel (AJO International)
Purpose: To determine rates of personal communication between patients and ophthalmologists. Design: This was a cross-sectional study assessing ophthalmologists’ electronic communication practices with patients in 2021. Methods: An online survey was distributed to a convenience sample of ophthalmologists through an ophthalmology email listserv in the United States. Results: Of 92 respondents, the average age was 55.2 (range: 32–86) and most were male (70.7 %) with >10 years of attending experience (81.5 %). Overall, 63.0 % of respondents shared their personal phone number or email address with patients, more frequently for post-operative patients (63.0 %) or patients with complications (52.2 %). Many respondents (55.4 %) did not discuss guidelines for using their personal email or phone number with patients and the majority (87.0 %) expressed little or no regret in sharing their contact information. Most ophthalmologists (76.1 %) endorsed reimbursement for extra time talking with patients outside of clinic appointments, while few (6.5 %) billed for their calls. Documentation of electronic encounters in the electronic medical record showed 44.6 % documenting most of the time and 30.4 % rarely documenting. Conclusion: Many ophthalmologists share their personal email address or phone number with patients without setting guidelines for patients using them or properly documenting and billing for the electronic encounter. This suggests a need for improved accessibility of physicians through office phone numbers. Additionally, guidelines may be warranted to support ophthalmologists in documenting and billing for electronic communications for patient safety and medicolegal purposes.